Evaluation of CIMMYT maize (Zea mays L.) germplasm by tropical inbred testers (Bangladesh Journal of Botany, 2015)
Twenty five CIMMYT inbreds were crossed with four elite tropical maize testers. Results exhibited that one inbred line tester can select the top best lines from a large number of CIMMYT lines and two testers gave more reliable results than one tester did. However, when line × environment interaction was significant, selected lines by one tester in one environment were not necessarily same as those selected at another environment indicating thereby that different testers should be used for selecting best inbreds at different environments. This study also showed that inbred lines from different maize heterotic groups did not show any significant differences in identifying best CIMMYT germplasm DOI: http://dx.doi.org/10.3329/bjb.v43i2.21661 Bangladesh J. Bot. 43(2): 131-139, 2014 (September)